Assessment of The Use of Writing Skills Methods in Second Grade Elementary School Students - Farihiyah Farihiyah (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the implementation of writing skills teaching methods in daily learning practices, identify and describe the methods used by teachers, and understand how teachers evaluate and provide feedback on the development of students' writing skills. The research approach used was qualitative with descriptive methods. The subjects were first-grade students of SD Negeri 4 Segeran and their class teachers as the main informants. Data were obtained through in-depth interviews and documentation, then analyzed using data reduction, data presentation, and conclusion drawing according to the Miles and Huberman model. The results showed that first-grade teachers implemented various writing learning methods, such as demonstrations, guided practice, small group discussions, and the use of visual media. These methods were adapted to students' cognitive development, thus helping them develop ideas, construct simple sentences, and correct spelling errors. Evaluation was carried out by assessing the writing process and results, while feedback was provided directly, both verbally and in writing, to strengthen student motivation. The conclusion of this study confirms that the diversity of learning methods and teacher evaluation practices contribute positively to the writing skills of first-grade students. These findings are expected to serve as a reference for teachers in developing effective, adaptive, and enjoyable literacy learning strategies in elementary education.